Managerial Styles of Executives - A Study of Manufacturing Companies of Punjab - Singh, Navpreet; Singh , Sukhjeet (Gyan Management Journal, 2011)
.'vfanagers are the pillars of an organization and on them depends its success. For an organization to be effective, the managerial approach to decision making, along with technological efficiency and facilities available for research and development, is very important. The distinctive way in which various functions such as goal setting, strategy formulation and implementation, organizing, staffing, control, co-ordination, leadership, image building, etc. are performed comprises the managerial style. It associates with superior organizational /earning, smoothness of functioning, managerial development, synergy, performance etc. Those styles, which have damaging effect on the overall health af the organisation, can be easily diagnosed and discontinued, with immediate effect. A diagnostic nstrument with a scoring key helps the management to diagnose how far excellent and bad styles are practiced in their organisation so that the best style can be made use of and the bad ones avoided. The present study was undertaken with an aim of understanding and comparing the managerial styles being used by executives at various levels in the manufacturing companies of Punjab. The outcome of
Keywords: Managerial Approach; Goal Setting; Organisational Learning; Synergy